A MINI REVIEW: SINTESIS DAN KARAKTERISASI NANOKOMPOSIT Fe3O4/ZnO SERTA APLIKASINYA - Apriliana, Nina; Hindryawati, Noor (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
The Fe3O4/ZnO nanocomposites have an interesting combination due to their constituent composition. Fe3O4 is a ferromagnetic material that can react with magnetic fields, while ZnO is a semiconductor material that has a large band gap and strong photocatalytic properties. This article aims to analyze research on Fe₃O₄/ZnO nanocomposites and their applications. Based on several articles, Fe₃O₄/ZnO nanocomposites can be made using several methods including sonochemical, co-presipitasi, sol-gel, hydrothermal, ultrasonication, solid-state, layer-by-layer self assembly and poliol methods. Characterization can be done using XRD (X-Ray Diffraction), SEM (Scanning Electron Microscope) and TEM (Transmission Electron Microscope) instruments. The Fe3O4/ZnO nanocomposites can be used as photocatalysts for dyes, antibiotics and p-nitrophenol. The ability of Fe₃O₄/ZnO nanocomposites in photocatalysis can vary depending on several factors such as pH, contact time, concentration of Fe₃O₄/ZnO nanocomposites or degraded substances, etc. In addition, Fe₃O₄/ZnO nanocomposites can also act as antibacterial agents that have quite good activity on several bacteria, namely Eschericia coli. (-), Bacilis subtilis. (+) and Staphylococcus aureus. (+). Keywords : Application, Nanocomposite, Synthesis